Life Protection and the Basic Rules of Using Firearms by the Police - Kapusta, Monika (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
The article analyzes the basic principles of the use of firearms by the Police in the context of protecting human life. The function of the Police is to protect certain legal goods, and the use of firearms poses a threat to these goods. This became the reason for an attempt to answer the question whether the rules introduced in the provisions of the Act of 24 May 2013 on direct coercion measures and firearms are absolutely applicable and whether they constitute a sufficient guarantee of protection of these goods, or whether the use of weapons will constitute a violation of the law regardless of the circumstances right to life.